Ebu'n-Nasayih of Muhammed bin Ahmed - (:unkn) unknown (ISAM, 2011)
This article introduces the treatise entitled Ebu'n-Nasayih (The Father of [works of] Advice) authored by a certain Muhammed bin Ahmed el-Kostantini, whose identity is presently unknown. Written in the nasihatname form, i.e., as a work of counsel or advice, it is a prose text comprised of eighty four proverbs (atasoz). In addition, some of the proberbs contain samples of Ottoman poetry. While undated, the text appears to have been written in the second half of the fifteenth or early sixteenth century. The work provides the context of the proverbs in terms of how they were understood. As such, it makes this manuscript one of the rare sources that examine Turkish proverbs in this period. The only known manuscript of this treatise is preserved in the manuscript collection of the library of the Department of Information and Document Management, Faculty of Arts and Letters, Marmara University.
Keywords: Muhammed bin Ahmed el-Kostantini; Ebu'n-Nasayih; Nasihatname / Advice literature